(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In today’s interconnected world, a strong sense of patriotism and civic responsibility among citizens is becoming increasingly important. Education plays a very important role in forming the values and views of a person towards his own nation. This article examines the importance of education for patriotism and the ways of its effective formation among students.